Several kinds of aminoxyl radicals and their metal ion complexes - Sugano, T; Blundell, S; Pratt, F; Jestadt, T; Lovett, B; Hayes, W; Day, P (1999)
Recent results of magnetization, magnetic susceptibility and muon spin rotation/relaxation (mu SR) measurements of some organic neutral radicals based on aminoxyl and their anion radical complexes with all;ali and transition metal cations are reported. Ferromagnetic intermolecular interactions, coexistent with antiferromagnetic ones, in several carboxyaryl nitronyl nitroxide radicals are affected by inserting alkali metal ions, while the incorporation of transition metal ions result in complex behavior suggesting in part ferromagnetic interactions. Temperature dependence of spontaneous magnetization of TANOL suberate in the ordered state, obtained through the results of mu SR measurements, is characteristic of a two-dimensional magnetic lattice, consistent with that of magnetic susceptibility above the ordering temperature.